2016
DOI: 10.1089/thy.2015.0315
|View full text |Cite
|
Sign up to set email alerts
|

An International Multi-Institutional Validation of Age 55 Years as a Cutoff for Risk Stratification in the AJCC/UICC Staging System for Well-Differentiated Thyroid Cancer

Abstract: A change in the cutoff age in the current AJCC/UICC staging system from 45 years to 55 years would lead to a downstaging of 12% of patients, and would improve the statistical validity of the model. Such a change would be clinically relevant for thousands of patients worldwide by preventing overstaging of patients with low-risk disease while providing a more realistic estimate of prognosis for those who remain high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(154 citation statements)
references
References 26 publications
6
139
1
8
Order By: Relevance
“…The wider the spread between the different categories is, the better the statistical power of the division between the groups is. As also shown recently by Nixon et al and Kim et al in this respect, some aspects of the new TNM system offer an improvement over version 7. Even though the lower risk category in TNM 8 encompasses a few more fatal cases than that in TNM 7, the dichotomization in two age categories in TNM 8 appears to yield a more powerful division than that in TNM 7.…”
Section: Discussionsupporting
confidence: 61%
“…The wider the spread between the different categories is, the better the statistical power of the division between the groups is. As also shown recently by Nixon et al and Kim et al in this respect, some aspects of the new TNM system offer an improvement over version 7. Even though the lower risk category in TNM 8 encompasses a few more fatal cases than that in TNM 7, the dichotomization in two age categories in TNM 8 appears to yield a more powerful division than that in TNM 7.…”
Section: Discussionsupporting
confidence: 61%
“…Functional enrichment analysis of identified PTC progression associated genes was performed using Enrichr [22, 23]. We analyzed protein-protein interaction using STRING [78] networks based on protein association knowledge from databases of physical interaction and databases of curated biological pathway knowledge (MINT, HPRD, BIND, DIP, BioGRID, KEGG, Reactome, IntAct, EcoCyc, NCI-Nature Pathway Interaction Database, GO) and predicted associations between genes based on observed patterns of simultaneous expression of genes [78].…”
Section: Methodsmentioning
confidence: 99%
“…The vast majority of the downstaged patients (97%) were then considered as having stage I disease, and the disease-specific survival rate of this newly defined group of patients was 98% at 10 years of follow-up [13]. This analysis suggested that using an age cutoff of 45 years would lead to a significant number of patients who are at very low risk of death being inappropriately assigned an advanced disease stage [14]. The American Thyroid Association (ATA), the Latin American Thyroid Society (LATS), and the European Thyroid Association (ETA) guidelines for the follow-up and treatment of DTC have recommended the use of the TNM staging system mainly to predict the probability of DTC-related death [15,16,17].…”
Section: Introductionmentioning
confidence: 99%